The Gender of Debt and Credit: Insights from Rural Tamil Nadu - Isabelle Guérin; Christophe Jalil Nordman; Elena Reboul (Institute of Labor Economics (IZA), 2020)
The champions of financial inclusion regret women's lack of access to credit, while critics of financialization, by contrast, claim that women have become overly indebted. But little is actually known about women's debt/credit in quantitative terms, mostly due to a lack of data. This descriptive paper uses first-hand survey data from southern India disaggregated by sex in order to analyze the gender of debt and its interplay with caste and poverty, based on descriptive statistics and econometric results. We show that women are heavily indebted, first and foremost to informal sources, alongside microcredit. While men are much higher earners, they borrow much less in relative terms. Furthermore, women prominently - and markedly more so than men - borrow in order to make ends meet; productive investment largely remains a male practice. Lastly, women of the poorest and lowest-caste households have the heaviest borrowing responsibilities, managing the highest proportions of household debt. On a theoretical level, these results highlight the gendered earmarking of debt and credit: male and female debts/credits do not have the same meanings and uses. They also confirm the gendered dimension of behavior, in as much as women's behavior is constrained by family affiliation, poverty level and caste, all of which affects men much less. Last, in terms of policy implications, these results put into question the specific targeting of women by microcredit policies, likely to strengthen the association between debt and poverty for women, and in particular to exacerbate female responsibilities for managing scarcity.
Keywords: G51; O16; J16; D14; 330; gender; debt; poverty; caste; microcredit; India